ANALISIS ASUMSI KLASIK TERHADAP FAKTOR-FAKTOR PRODUKTIVITAS KERJA TENAGA PEMANEN DI PERKEBUNAN KELAPA SAWIT - Tarigan, Putrisina Br (Agriprimatech, 2023)
In analyzing productivity, appropriate methods are needed to answer hypotheses in a study. The classical assumption test is an analysis carried out to assess whether in a linear regression model there are problems with the classical assumptions. This research aims to determine the linear relationship between the observed variables. This research uses a qualitative descriptive method with classical assumption tests on productivity with the variables age (X1), salary (X2), and dependents (X3). The results of this study show that the regression model has a normal distribution, there are no symptoms of heteroscedasticity, no symptoms of multicollinearity and no symptoms of autocorrelation with productivity.